Monocyte-derived extracellular Nampt-dependent biosynthesis of NAD(+) protects the heart against pressure overload - Yano, Masamichi (Sci Rep, 2015)
Nicotinamide phosphoribosyltransferase (Nampt) catalyzes the rate-limiting step in the salvage pathway for nicotinamide adenine dinucleotide (NAD(+)) biosynthesis, and thereby regulates the deacetylase activity of sirtuins. Here we show accommodative regulation of myocardial NAD(+) by monocyte-derived extracellular Nampt (eNampt), which is essential for hemodynamic compensation to pressure overload. Although intracellular Nampt (iNampt) expression was decreased in pressure-overloaded hearts, myocardial NAD(+) concentration and Sirt1 activity were preserved. In contrast, iNampt was up-regulated in spleen and monocytes, and circulating eNampt protein and nicotinamide mononucleotide (NMN), a key precursor of NAD(+), were significantly increased. Pharmacological inhibition of Nampt by FK866 or depletion of monocytes/macrophages by clodronate liposomes disrupted the homeostatic mechanism of myocardial NAD(+) levels and NAD(+)-dependent Sirt1 activity, leading to susceptibility to cardiomyocyte apoptosis and cardiac decompensation in pressure-overloaded mice. These biochemical and hemodynamic defects were prevented by systemic administration of NMN. Our studies uncover a crucial role of monocyte-derived eNampt in myocardial adaptation to pressure overload, and highlight a potential intervention controlling myocardial NAD(+) against heart failure.